Neonatal mortality and risk factors in the state of Paraná: temporal trend from 2000 to 2016 (Research, Society and Development, 2022)
To analyze the series of neonatal mortality rates in the state of Paraná and risk factors between 2000 and 2016. This is an ecological-descriptive-analytical study using Quasi-Poisson and Gaussian regression models. The factors gender and age of the child were considered; age and education of the mother. Neonatal and early neonatal mortality rates were, on average, higher for boys at approximately 2.6 and 2.4 deaths per 1,000 live births, respectively, reduction of one death every eight years for girls and one death every four years for boys at both rates. Every five years the early neonatal mortality rate decreased by 16% for mothers up to 19 years old and 12% for mothers over 19. For neonatal mortality rate there was a decrease of 11% every five years in both age groups. Among mothers with up to seven years of education, there is a drop of 6% in the neonatal mortality rate and 11% at the beginning, every five years. In all cases the late neonatal mortality rate was not significant. There was a significant reduction in the neonatal mortality rate in the state of Paraná in any period evaluated, with early neonatal mortality emerging as the main component of the decay; late neonatal mortality remained constant. On average, the risk of neonatal death is higher for boys; for babies whose mothers are up to nineteen and among newborns of mothers with up to seven years of schooling.